Rapid conversion of Histoplasma capsulatum, Blastomyces dermatitidis and sporothrix schenckii in tissue culture. - Hempel, H (1975)
A simple method for positive identification of Histoplasma capsulatum, Blastomyces dermatitidis, and Sporothrix schenckii is given. Primary tissue cultures of guinea pig peritoneal macrophage were inoculated with the mycelial phase of each organism and after 24 h the cells were stained and observed microscopically. The characteristic yeast phase could then be observed allowing for positive identification.